Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1958
DOI: 10.1063/1.1744111
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Gas Phase Halogenation Reactions

Abstract: Rate constants for the gas-phase reactions of OH radicals with ethylene and halogenated ethylene compoundsMaking use of the independently measured rate constants for the reactions X+X+M~X.+M (where X=Br, I, etc.) it is possible to calculate the times needed to approach the stationary state for X atoms. On applying these results to the kinetic studies which have been made of halogenation reactions, it is found that for most thermal brominations, the times are in excess of 100 seconds. For thermal chlorinations,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1968
1968
1999
1999

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The conditions under which such a n equilibrium is established have been closely examined [4] for I, , C1, , and other systems. It is clear from this study that, since in practice no induction period is ever observed in I, + R H systems, the dissociation and association of I, takes place, at least partly, on the surface by some heterogeneous mechanism.…”
Section: A Ic1 As a Thermal Source Of Chlorine Atommentioning
confidence: 99%
“…The conditions under which such a n equilibrium is established have been closely examined [4] for I, , C1, , and other systems. It is clear from this study that, since in practice no induction period is ever observed in I, + R H systems, the dissociation and association of I, takes place, at least partly, on the surface by some heterogeneous mechanism.…”
Section: A Ic1 As a Thermal Source Of Chlorine Atommentioning
confidence: 99%
“…Reactions of small hydrocarbon free radicals (such as CH 3 , C 2 H 5 , C 3 H 7 , C 4 H 9 ) with hydrogen halides (HI, HBr, and HCl) have been a subject of research during the last 50 years. Beyond their importance for the fundamental chemical kinetics, these kinetic measurements were used as a source of the C−H bond energies . Combination of the rate constant of reaction of a free radical with hydrogen halide with the rate constant of the reverse reaction, reaction of the halogen atom with the corresponding hydrocarbon molecule, yields a temperature-dependent equilibrium constant.…”
Section: Introductionmentioning
confidence: 99%
“…Bromine reactions chains are shorter because propagation step 2 has a larger activation energy than the same step for chlorine reactions.17 Similar long chains occur in other photobrominations of various gaseous hydrocarbons. 18 A quantum yield of 30-40 was reported by Jost19 in 1931 for the gas phase photobromination of cyclohexane. Except for this last example, chain lengths larger than 103 Br2 consumed per photon absorbed are evidence of low activation energies for the chain carrying steps.…”
Section: Resultsmentioning
confidence: 92%